Conidae (Mollusca, Gastropoda) of Lakshadweep, India - Ravinesh, Raveendhiran; Kumar, Appukuttannair Biju; Kohn, Alan J. (Zootaxa, 2018)
Lakshadweep, the northernmost region of the Chagos-Maldives-Lakshadweep group of islands located southwest of the Malabar coast of India in the Arabian Sea, is the only chain of coral atolls in India. This paper documents the diversity of the molluscan family Conidae from the seas around all ten inhabited islands of Lakshadweep. Of the 78 species of cone snails now reported from Lakshadweep, 49 were recorded in this study. Three of these had not previously been reported from India, and four are newly reported from Lakshadweep. The results increase the number of Conidae species known from Lakshadweep by 10%.